Marketing in the 21st Century. - Emerald Group Publishing (Emerald Group Publishing, 2004)
Back in the 1960s, a marketing revolution took place. Primarily driven by the introduction of the television into millions of homes across America and Europe, companies quickly began to realize the potential of this new medium for selling products. On the back of this, marketing became extremely influential - a "wunderkind driving corporate strategy and growth" according to 3M marketing director Allan J. Magrath. Whilst the golden age of marketing may have dimmed somewhat, there is little doubt about the influence it still holds. Even so, the harsh changes wrought upon the business world through the effects of terrorism and economic hardship have led many organizations to ask themselves searching questions about the ways in which they interact with their customers. For sure the new media revolution has opened up many avenues of opportunity, but it has also contributed significantly to today's syndrome of "information overload." In this environment, companies have a tough job on their hands. Use this Management Briefing to make sure you keep abreast of all of the latest developments.